Manajemen Pembelajaran Literasi Digital Guna Meningkatkan Kreativitas Siswa SMPN 11 Kota Sukabumi dengan Menggunakan Aplikasi Canva - Sofyani, Ani; Mutia Agustina, Mutia Agustina; Ade Anwar Mutakin, Ade Anwar Mutakin; Neng Yunita Nurmala, Neng Yunita Nurmala (Wali Pikir: Journal Of Education, 2024)
This research is motivated by the lack of student motivation in literacy, especially as the current digital generation, students' learning styles must be varied and more enjoyable. The general aim of the research is to find out and analyze digital literacy management in order to increase student creativity using the Canva application, while the specific aim is to find out and analyze planning to increase enthusiasm for learning, implementing learning as a more interactive learning experience, and evaluating the results of student creativity. evaluation research method with a qualitative approach. Using the Canva application provides significant benefits for students, not only helping to improve literacy skills but also creating a more interactive learning experience resulting in student creativity with graphic design that produces work with an attractive visual appearance and this is the answer to our research that with Using the Canva application is able to increase the digital literacy creativity of students at SMPN 11 Sukabumi City and their ability to use technology on a daily basis, especially in creating more focused visuals with the Canva application.